Educational differences in mortality and the relative importance of different causes of death: a 7-year follow-up study of Spanish adults. Issue 12 (14th August 2014) - Reques, Laura; Giráldez-García, Carolina; Miqueleiz, Estrella; Belza, María J; Regidor, Enrique
Abstract : Background: The evidence on mortality patterns by education in Spain comes from regional areas. This study aimed to estimate these patterns in the whole Spanish population. Methods: All citizens aged 25 years and over and residing in Spain in 2001 were followed during 7 years to determine their vital status, resulting in a total of 196 470 401 person-years and 2 379 558 deaths. We estimated the age-adjusted total and cause-specific mortality by educational level—primary, lower secondary, upper secondary and university education—and then calculated the relative and absolute measures of inequality in mortality and contribution of the leading causes of death to absolute inequalities. Results: Except for some cancer sites, the mortality rate for the leading causes of death shows an inverse gradient with educational level. The leading causes of death with the highest relative index of inequality ratios were HIV disease (9.81 in women and 11.61 in men), diabetes in women (4.02) and suicide in men (3.52). The leading causes of death that contribute most to the absolute inequality in mortality are cardiovascular diseases (48.8%), respiratory diseases (9.3%) and diabetes mellitus (8.8%) in women, and cardiovascular diseases (20.8%), respiratory diseases (19.8%) and cancer (19.6%) in men. Conclusions: Although the causes of death with the strongest gradient in mortality rate are HIV disease in both sexes, diabetes mellitus in women and suicide in men, most of the absolute education-related inequalities in total mortality are due to cardiovascular diseases, respiratory diseases and diabetes mellitus in women and to cardiovascular diseases, respiratory diseases and cancer in men.